Eksperimen Pembelajaran Matematika Dengan Modelcorse Review Horay Dan Number Head Togrther Terhadap Hasil Belajar Ditinjau Dari Keaktifan (Pada Siswa Kelas Viii Semester Ganjil Smp N 1 Sambi Tahun 2016/2017) - Nugroho, Agung, Dra. Sri Sutarni,M.Pd (2017)
This study aims to examine (1)theeffect of mathematics learning withNumbered Head Together and Course Review Horay models on the result of mathematical learning , (2) the effect of students' learning activeness on the result of mathematical learning, (3) the interaction between the Numbered Head Together and Course Rfeview Horay models seen from the students activeness on mathematics learning. The type of the research is experiment with quasi experimental design.The population of the research was all students of VIIIGrade of SMP N 1 Sambiyear 2016/2017.The research sample consisted of two classes namely VIII A grade as Numbered Head Together class and VIII B grade as Course Review Horay. The sampling technique used is cluster random sampling. Technique of collecting data with method test, questionnaire method, and documentation. Technique for analyzing data uses is two-way analysis of variance test with unequal cells, previously performed prerequisite analysis to test for normality and homogeneity test. From the results of data analysis at the level of 5% was obtained that: (1) there is effect of Numbered Head Together and Course Review Horay models on the result of mathematics learning withF_A=17.151 (2) there is effect of students' learning activeness on the result of mathematics learning with F_B=143.095(3) there is no interaction between of Numbered Head Together and Course Review Horaymodels seen of the students' learning activeness on the result of mathematics learning withF_AB=1.482 Keywords : Course Review Horay,the resultlearning, learning activeness, Numbered Head Together.